Extraction of Alkaloids for NMR-Based Profiling: Exploratory Analysis of an Archaic Cinchona Bark Collection - Yilmaz, Ali; Nyberg, Nils T.; Jaroszewski, Jerzy W. (Planta Medica, 2012)
A museum collection of Cinchonae cortex samples (n = 117), from the period 1850–1950, was extracted with a mixture of chloroform-d1, methanol-d4, water-d2, and perchloric acid in the ratios 5 : 5 : 1 : 1. The extracts were directly analyzed using 1H NMR spectroscopy (600 MHz) and the spectra evaluated using principal component analysis (PCA) and total statistical correlation spectroscopy (STOCSY). A new method called STOCSY-CA, where CA stands for component analysis, is described, and an analysis using this method is presented. It was found that the samples had a rather homogenous content of the well-known cinchona alkaloids quinine, cinchonine, and cinchonidine without any apparent clustering. Signals from analogues were detected but not in substantial amounts. The main variation was related to the absolute amounts of extracted alkaloids, which was attributed to the evolution of the Cinchona tree cultivation during the period in which the samples were collected.
Keywords: Cinchona; Rubiaceae; alkaloids; NMR; profiling; PCA; STOCSY; STOCSY-CA